Differential expression of genes in replicative (spiral) and persistent (biofilms) forms of the causative agent of human Lyme borreliosis - Vranjes, Sabrina (Jihočeská univerzita, 2023)
The onset and development of post treatment Lyme disease syndrome (PTLDS) remains a constant challenge in the diagnosis and treatment of Lyme borreliosis (LB). The driving force behind this is the formation of persisters cells, which are able to hide within the host, "invisible" to the immune system and resistant to antibiotic treatment. Thus far, few types of persisters have been found to be formed by the Borrelia burgdorferi spirochete, with biofilms being one of them. Multiple atypical forms of spirochetes often are uneasy to be detected via the average testing methods, leading to many cases being misdiagnosed. Additionally, the formation of biofilms, as a resilient complex community of cells, has not only been observed in case of Lyme disease, but also in other illnesses worldwide. This thesis deals with the analysis of genes differentially expressed in biofilms in comparison to the replicating forms of spirochetes, with aim to better understand the formation of these morphotypes.
Differential expression of genes in replicative (spiral) and persistent (biofilms) forms of the causative agent of human Lyme borreliosis
Keywords: Lyme Borreliosis; spirochetes; persistent morphotypes; differential gene expression; Post treatment lyme disease syndrome; Lyme Borreliosis; spirochetes; persistent morphotypes; differential gene expression; Post treatment lyme disease syndrome